A Comparative Study of Shaping Ability of four Rotary Systems - Jorge Rubio; Jose Ignacio Zarzosa; Antonio Pallres (University of Zagreb. School of Dental Medicine, 2015)
Purpose: This study compared the cutting area, instrumentation time, root canal anatomy preservation and non-instrumented areas obtained by F360®, Mtwo®, RaCe® and Hyflex® files with ISO size 35. Material and Methods: 120 teeth with a single straight root and root canal were divided into 4 groups. Working length was calculated by using X-rays. The teeth were sectioned with a handpiece and a diamond disc, and the sections were observed with Nikon SMZ-2T stereoscopic microscope and an Intralux 4000-1 light source. The groups were adjusted with a preoperative analysis with AutoCAD. The teeth were reconstructed by a #10 K-File and epoxy glue. Each group was instrumented with one of the four file systems. The instrumentation time was calculated with a 1/100 second chronometer. The area of the thirds and root canal anatomy preservation were analyzed with AutoCAD 2013 and the non-instrumented areas with AutoCAD 2013 and SMZ-2T stereoscopic microscope. The statistical analysis was made with Levene's Test, ANOVA, Bonferroni Test and Pearson´s Chi-square. Results: Equal variances were shown by Levene's Test (P > 0.05). ANOVA (P > 0.05) showed the absence of significant differences. There were significant ifferences in the instrumentation time (P < 0.05). For root canal anatomy preservation and non-instrumented areas, there were no significant differences between all systems (P > 0.05). Conclusions: The 4 different rotary systems produced similar cutting area, root canal anatomy preservation and non-instrumented areas. Regarding instrumentation time, F360® was the fastest system statistically.